ANALISIS KELAYAKAN BUKU TEKS SISWA IPA KURIKULUM 2013 PADA MATERI PENCEMARAN LINGKUNGAN KELAS VII DITINJAU DARI KELENGKAPAN DAN KETEPATAN ISI - Yusa, Ilham Widia; Septiana, Eriza Ika; Susanti, Ariska Putri (Universitas Esa Unggul, 2021)
This study aims to identify the completeness and accuracy of the contents of the 2013 curriculum science student textbooks on environmental pollution material in grade VII. The method used in this research is a qualitative approach. From the results of the analysis, it was found that the completeness of the contents of the 2013 curriculum science student textbook on environmental pollution material for grade VII was considered incomplete, this was due to the fact that there were still some sub-materials that had not been included. As for the accuracy of the contents of the book, it can be said that it is quite in accordance with the indicators of KD achievement from KI-1, KI-2, KI-3 and KI-4. This is evidenced by the suitability of the content of the book which is sufficient to meet the KD achievement indicators from KI. Based on the results of the analysis, it can be said that the student textbook is feasible as teaching material but still requires improvement. Keywords: Student Textbooks, Completeness of Content, Accuracy of Content, Teaching Materials, 2013 Curriculum